Climate change and Food Heritage: Lessons on Resilience (PerCursos, 2021)
The COVID global public health crisis has increased the risks related to human life on planet Earth, increasing the importance of creating joint solutions considering climate change mitigation, food production, biodiversity conservation and public health. In this article various lessons on resilience regarding climate change and food security are presented from different social groups in Brazil and Spain are presented. These cases, which involve traditional knowledge and practices in the production and preparation of food stuff , argue in favor of the importance of such practices in bring forth agricultural resilience and assisting in the mitigation of the impacts of climate change. The article is structured around three axis of discussion: the first presents the concept of agricultural and food heritage and the legal frameworks that govern it in Brazil, Spain and worldwide. The second topic presents the relationship between climate change and traditional knowledge and practices associated with agro-systems, and the third topic discusses the relationship between the issue of climate change and food practices.
Keywords: biodiversity; food; heritage; climate change